The National SOM Survey 1987 - SOM Institute, University of Gothenburg (University of Gothenburg, 1989)
This dataset contains information from the second SOM-survey. The questionnaire was divided into seven subject fields: Mass media; politics and society; energy and nuclear power; Sweden´s relation to other countries; housing and interests; social background; and music. Many of the questions are replications of questions asked in SOM86, some of the questions put in SOM86 are excluded and a number of questions are added. These new questions deal with: important content in morning papers; etical rules in news service; advertisement; the most important problems of society; quality of party leaders; privatisation; government control of municipalities, trade and industry, and the individual; confidence in different groups in regard to foreign policy; government consideration to different groups in regard to foreign policy; televison treatment of those in power in a number of countries; comparisons between morning papers and television; respondent´s activities during the last 12 months; statements about respondent´s work; changes in the economic situation for the respondent and for the country; and music listening.

Purpose:

The main purpose is to establish time series that enable researchers to analyse how various changes in society affect people's attitudes and behaviour.

Detta är den andra undersökningen i serien Riks-SOM, en nationell frågeundersökning med syfte att kartlägga den svenska allmänhetens vanor och attityder på temat samhälle, opinioner och medier.

1987 års undersökning var indelat i sju ämnesområden: Massmedier; politik och samhälle; energi och kärnkraft; Sveriges förhållande till andra länder; boende och intressen; bakgrundsfrågor; och musik.

Många av frågorna ställdes även i 1986 års undersökning, men ett antal frågor har tillkommit. De nya frågeställningarna tar bland annat upp: viktigt innehåll i morgontidningar; etiska regler i nyhetsrapportering; reklam; de viktigaste problemen i samhället; egenskaper hos några av partiledarna; privatisering; statlig kontroll av kommuner, näringsliv och enskilda; förtroende för olika grupper i frågor som rör utrikespolitiken; regeringen hänsyn till olika grupper i frågor som rör utrikespolitik; TV:s behandling av de styrande i ett antal länder; jämförelser mellan morgontidningar och tv; respondentens aktiviteter under de senaste 12 månaderna; arbetsförhållande; förändringar i den egna ekonomiska situationen respektive den svenska ekonomin; och musiklyssnande.

Genom att frågor ställts på ett likartat sätt över tid finns det i SOM-serien tidsserier om bland annat medieanvändning, politik, kärnkraftsopinion och förtroende för olika samhällsinstitutioner och grupper.

Syfte:

Huvudsyftet är att etablera tidsserier som gör det möjligt att analysera hur olika samhällsförändringar påverkar människors attityder och beteenden.
Den nationella SOM-undersökningen 1987
Riks-SOM 1987
Keywords: elections; val; housing; boende; mass media; massmedia; defence; försvar; participation; deltagande; public sector; offentlig sektor; international relations; internationella relationer; energy; energi; environment; miljö; planning; planering; leisure time; fritid; job satisfaction; arbetstillfredsställelse; political interest; politiskt intresse; nuclear energy; kärnkraft; newspaper readership; tidnings läsekrets; membership; medlemskap; listening to music; musiklyssnande; state control; statlig styrning; television news; tv-nyheter; energy policy; energipolitik; radioactive wastes; radioaktivt avfall; equipment; utrustning; local press; lokalpress; professional ethics; yrkesetik; foreign policy; utrikespolitik; economic aid; ekonomiskt bistånd; privatization; privatisering; advertising; reklam; press advertising; tidningsreklam; economic conditions; ekonomiska villkor; risk; risk; internal politics; inrikespolitik; political parties; politiska partier; political leaders; politiska ledare; leisure time activities; fritidsaktiviteter; organizations; organisationer; refugees; flyktingar; CORS; CORS; Media; Media; Environment and conservation; Miljö och naturvård; Energy and natural resources; Energi och naturresurser; Political behaviour and attitudes; Politiska beteenden och attityder; International politics and organisations; Internationell politik och organisationer; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap